Organic–inorganic hybridized zeolite by polycardanol for ammonia-nitrogen adsorption. Issue 3 (1st February 2021) - Gao, Chuan; Yu, Ruobing; Huang, Jian
Abstract: In order to remove the ammonia nitrogen in wastewater, a novel organic-inorganic hybridized zeolite was prepared. Polycardanol (a long-chain acid) was synthesized at first, and the organic-inorganic hybridized zeolite was obtained by the reaction between the zeolite and polycardanol, which results in long-chain branched zeolite (Z–P). The adsorption of Z-P for ammonia-nitrogen in simulated water was also investigated. Z–P was characterized with scanning electron microscopy/energy dispersive spectrometer (SEM-EDS), X-ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS) and Fourier transform infrared spectroscopy (FT-IR). Compared with zeolite, the surface of Z–P is relatively rough and the density (1.1 g/cm³) is low. Z–P has higher adsorption capacity (13.56 mg/g) for ammonia nitrogen than zeolite (3.94 mg/g), which is due to the multi-adsorption mechanisms including ion exchange and chemical precipitation. Langmuir isotherm and Pseudo-second order model could describe the adsorption process of Z–P, indicating that the adsorption is a single-layer homogeneous adsorption process. The ammonia-nitrogen adsorption process of Z-P is spontaneous and endothermic. Graphical Abstract: